Phase I studies of the safety, tolerability, pharmacokinetics and pharmacodynamics of the dual glucagon receptor/glucagon‐like peptide‐1 receptor agonist BI 456906. Issue 4 (30th January 2023) - Jungnik, Arvid; Arrubla Martinez, Jorge; Plum‐Mörschel, Leona; Kapitza, Christoph; Lamers, Daniela; Thamer, Claus; Schölch, Corinna; Desch, Michael; Hennige, Anita M.
Abstract: Aim: To report two phase I studies of the novel subcutaneous glucagon‐like peptide‐1 receptor/glucagon receptor (GLP‐1R/GCGR) dual agonist BI 456906 versus placebo in healthy volunteers and people with overweight/obesity. Materials and Methods: A phase Ia study (NCT03175211) investigated single rising doses (SRDs) of BI 456906 in 24 males with a body mass index (BMI) of 20–<30 kg/m 2 . A phase Ib study (NCT03591718) investigated multiple rising doses (MRDs) of BI 456906 (escalated over 6 [Part A] or 16 [Part B] weeks) in 125 adults with a BMI of 27–40 kg/m 2 . Results: In the SRD study (N = 24), mean body weight decreased with increasing BI 456906 dose. In the MRD study, the maximum decreases in placebo‐corrected mean body weight were at week 6 (–5.79%, dosage schedule [DS] 1; Part A) and week 16 (–13.8%, DS7; Part B). BI 456906 reduced plasma amino acids and glucagon, indicating target engagement at GCGRs and GLP‐1Rs. Drug‐related adverse events (AEs) increased with BI 456906 dose. The most frequent drug‐related AE with SRDs was decreased appetite (n = 9, 50.0%), and two subjects (8.3%) did not complete the trial because of AEs (nausea and vomiting). During MRD Part A (N = 80), 10 subjects (12.5%) discontinued BI 456906, most commonly because of a cardiac or vascular AE (n = 6, 7.5%); during Part B (N = 45), eight subjects (17.8%) discontinued BI 456906, mainly because of AEs (n = 6, 13.3%), most commonly gastrointestinal disorders. Conclusions: BI 456906 produced a placebo‐corrected body weight loss of 13.8% (week 16), highlighting its potential to promote clinically meaningful body weight loss in people with overweight/obesity.